2009
DOI: 10.7202/000378ar
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Pacific Coast wireworm, Limonius canus, and the dusky wireworm, Agriotes obscurus (Coleoptera: Elateridae), to insecticide-treated wheat seeds in a soil bioassay

Abstract: Larvae of the dusky wireworm, Agriotes obscurus, and the Pacific Coast wireworm, Limonius canus, were exposed to germinated, insecticide-treated wheat seeds in a soil-filled bioassay in 2005 and 2006. Position in the bioassay and contact and/or repellence behaviour towards the seeds were recorded every 5 min for 3 or 5 h. Wireworm health was recorded for 70 or 126 d after exposure. Seeds were treated with the fungicides Dividend XLRTA (difenoconazole, mefenoxam) or Raxil MD (tebuconazole, metalaxyl), and/or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…The proportion of L. canus wireworms placed in bioassay arenas that contacted seeds within 3 h (range 0.75-0.85; mean: 0.82; control treatment: 0.86; Table 2), and the time required to first contact seeds (range 38.4-59.3 min) did not differ significantly among treatments, and was similar to that observed in previous studies (van Herk et al 2008aHerk et al , 2010. There was no significant difference between treatments in the proportion of wireworms that had contacted seeds within 24 h (Table 2; Chi = 0.94, df = 4, P = 0.92).…”
Section: Contact Behavioursupporting
confidence: 84%
See 3 more Smart Citations
“…The proportion of L. canus wireworms placed in bioassay arenas that contacted seeds within 3 h (range 0.75-0.85; mean: 0.82; control treatment: 0.86; Table 2), and the time required to first contact seeds (range 38.4-59.3 min) did not differ significantly among treatments, and was similar to that observed in previous studies (van Herk et al 2008aHerk et al , 2010. There was no significant difference between treatments in the proportion of wireworms that had contacted seeds within 24 h (Table 2; Chi = 0.94, df = 4, P = 0.92).…”
Section: Contact Behavioursupporting
confidence: 84%
“…A small proportion (0.11-0.18) of larvae exposed to seeds treated with bifenthrin at 20 g and tefluthrin at both 10 and 20 g were moribund at 1 DAE, but these all had recovered by 7 DAE and there was no subsequent mortality. This rapid recovery from pyrethroid intoxication was previously observed for both A. obscurus and L. canus exposed to tefluthrin at 10 or 20 g (van Herk and Vernon 2007a;van Herk et al 2008a).…”
Section: Post-contact Wireworm Healthmentioning
confidence: 51%
See 2 more Smart Citations
“…Vernon et al (2008) found mortalities of A. obscurus and A. sputator dermally exposed to clothianidin and imidacloprid comparable to chlorpyrifos. However, in a soil-filled bioassay wireworm mortality was low (< 50%) when being exposed to insecticide-treated wheat seeds (clothianidin, thiamethoxam, imidacloprid) (van Herk et al 2008a). In contrast, van Herk et al (2008b) observed neither a toxic nor a repellent effect of those particular neonicotinoids in a soil-less bioassay.…”
Section: Neonicotinoidsmentioning
confidence: 90%